A Study of the Relationship between Cyber Bullying Behaviour and SES of Secondary School Students - Pandey, Anchal; Sonker, Sanjay (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Cyber bullying has been defined as “an aggressive act of behavior that is carried out by using electronic means by a group or an individual repeatedly and over time against a victim who cannot easily defend him or her The present study aimed to find out the relationship of Cyber Bullying behavior (CBB) with SES (age, family type and family income) among Government – aided and Private Secondary School Students (GASSS and PSSS) belonging to Varanasi city. 400 samples (200 GASSS and 200 PSSS) were selected randomly studying in class 9th to 12th of Secondary Schools of Varanasi city. Self made tool named Bullying behavior Assessment Questionnaire (BBAQ) used for data collection. Karl Pearson correlation coefficient value was used for the analysis of the data. The major findings were as Negative correlation was found between CBB and age, positive correlation was found between CBB with family type and family income among government-aided secondary school students. Positive correlation was found between CBB with age and family income whereas negative correlation was found between CBB and family type among private secondary school students. Negative correlation was found between CBB with age and family type whereas positive correlation was found between CBB and family income among secondary school students of Varanasi city.
Keywords: Cyber bullying behavior; age; family type; family; income; secondary school students